G340(P) Paediatric major incident planning. (May 2019) - Bird, R; O'Neill, B; Parikh, A; Pah, G; Lowlor, J; Edmonds, N
Abstract : In light of the recent terrorist attacks in London and Manchester we wanted to test our Major incident (MI) protocol for paediatrics using a simulated exercise (SIM). A hospital wide MI SIM was completed in January 2018 but focused on admission pathways, flow and theatre utilisation. As a follow up exercise, we wanted to test discharge pathways and our immediate bed capacity in PICU and paediatrics. The AIMS of the exercise were to:- Assess immediate capacity Estimate discharges from PICU/Wards Test Communication pathways Identify problems/issues Test staff call in responses Test awareness of next shift planning A MI pathway focussing on 'rapid discharge for admission' was designed with staff allocated to area based information points for allocation of roles. Method: We ran a live exercise testing the new MI policy using current in patient demographics from bed boards and handover sheets to assess discharge capacity in real time for bleep holders and nurses in charge. Results/Conclusion: 33 in-patients were identified as potentially dischargeable during the exercise. 26 of these were felt to be immediately dischargeable with TTA's. This capacity should be adequate to accept paediatric patients in the event of a major incident, assuming PICU has the required space for critically unwell children. Our communication pathway for nursing staff also had a good response identifying 33 nurses able to attend work within 1 hour of the call allowing adequate shift planning for an ongoing response. Moving Forward This simulation allowed us to identify the need for a rolling sheet to provide basic information about patient demographics, diagnosis, treatment and outstanding jobs for patient's transfers to other wards. We created ward based MI Boxes each of which contain:- An updated paediatric MI protocol and action cards Printed carbon copy sheets for rapid TTA transcription, duplicated for notes, patient & MI Box. (This creates a record for later follow up) Emergency prescription pads for medication, reducing demands on pharmacy in the event of a MI Our research prior to this exercise highlighted that there was significantly less planning for rapid discharge in the event of PMI. This exercise had a massive educational impact on staff empowering them for future planning.